TRACES OF VILLAGE INSTITUTES AND TRADE UNION LIFE IN THE WORKS OF FAKIR BAYKURT - Sevim KARABELA ŞERMET (Fırat University, 2019)
Fakir Baykurt name in Turkish literature attracts attention with its works after 1950. Fakir Baykurt, one of the pioneers of the title of "Village Novel" in particular, is the writer of life and literature. The village novel in Turkish literature is popular from the beginning of the 1950s until the end of the 1970s. It is to illuminate the village and peasant life of the main aim of the works of Fakir Baykurt. Fakir Baykurt is an important name for Turkish literature as far as Turkish education is concerned. Fakir Baykurt has been a teacher throughout his life, but has long played an active role in union activities conducted by teachers, not content with the role of teacher / writer in life. He has been a founder and administrator for a long time within the movement of Turkish Teachers Union (TÖS) which is the first teacher organization. The name of the poor Baykurt is important not only for the history of literature but also for the History of Turkish National Education and History of Turkish Trade Unionism. It is known that Fakir Baykurt, which guides teachers in a sense by pioneering the organization of teachers, assumes a primary role in the struggle that teachers engage in. The village institutes that shape his life and the union activities that he engages in during his teaching career have been a great influence on the life as well as in the private life. In this study, the definition of a teacher-writer within the organization movement of Fakir Baykurt and his reflection on his works will be revealed.